2008
DOI: 10.1109/tmi.2008.915549
|View full text |Cite
|
Sign up to set email alerts
|

The Haemodynamics of Endovascular Aneurysm Treatment: A Computational Modelling Approach for Estimating the Influence of Multiple Coil Deployment

Abstract: This paper proposes a novel computational methodology for modelling the haemodynamic effects of endovascular coil embolization for cerebral aneurysms. We employ high-resolution 3-D angiographic data to reconstruct the intracranial geometry and we model the coiled part of the aneurysm as a porous medium, with porosity decreasing as coils are inserted. The actual dimensions of the coils employed are used to determine the characteristics of the porous medium. Simulation results for saccular aneurysms from the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 28 publications
4
60
0
Order By: Relevance
“…[19][20][21][22][23] Using state-of-the-art techniques, several studies have reported the influence of blood flow on the results of coil embolization for intracranial aneurysms. [24][25][26][27][28][29] In this study, we investigated the hemodynamics of basilar tip aneurysms with special attention to the volume of blood flow into aneurysms through the neck. In addition, we examined the correlation between the configuration of the parent arteries and the proportion of blood flow entering into the aneurysms.…”
mentioning
confidence: 99%
“…[19][20][21][22][23] Using state-of-the-art techniques, several studies have reported the influence of blood flow on the results of coil embolization for intracranial aneurysms. [24][25][26][27][28][29] In this study, we investigated the hemodynamics of basilar tip aneurysms with special attention to the volume of blood flow into aneurysms through the neck. In addition, we examined the correlation between the configuration of the parent arteries and the proportion of blood flow entering into the aneurysms.…”
mentioning
confidence: 99%
“…[2][3][4] CFD simulations have been used to gain insight into the patient-specific hemodynamics and could potentially assist rupture-risk assessment [5][6][7][8][9] and treatment planning. [10][11][12][13][14][15][16] Vascular models can be constructed through segmentation of 3DRA and CTA images. Compared with CTA, 3DRA produces images with higher contrast, higher spatial resolution, and lower visibility of bone, [17][18][19] which lead to better segmentation results 20 and superior anatomic accuracy.…”
mentioning
confidence: 99%
“…1). Coil bundles can be modeled as a porous zone in order to study intra-aneurysmal flow characteristics (19) (20) . However, we assumed the coil had been embolized and the porous zone between coils was filled with soft clots.…”
Section: Aneurysm Modelsmentioning
confidence: 99%
“…The hemodynamics of partially blocked aneurysms have been analyzed using a computational fluid dynamics (CFD) method (17) (18) . Furthermore, intra-aneurysmal hemodynamics have been investigated computationally by modeling coils as a porous medium (19) (20) . Thromboembolization inside the coils was simulated using a viscosity model, which was defined as a function of both residence time and clotting fluid concentration (21) .…”
Section: Introductionmentioning
confidence: 99%